Translational research in health technologies: A scoping review - Mayrink, Nadja N. V.; Alcoforado, Luís; Chioro, Arthur; Fernandes, Felipe; Lima, Thaisa S.; Camargo, Erika B.; Valentim, Ricardo A. M. (Frontiers in Digital Health, 2022)
Introduction: The current debate on the process of technological innovation points out as a challenge for universities consolidation of competencies that allow the generation and transfer of knowledge to society. The Translational Research (TR) approach has as one of its main objectives the acceleration of the innovation process, based on the transposition from basic science to applied science and innovation, which comprises the different stages of research, development and innovation. The literature points out that the dynamics of translation, which results in new technologies, are complex, transdisciplinary, inter-institutional, systemic, and non-linear. The main objective of this review is to contribute to the adoption of institutional strategies and the formulation of public policies aimed at solving today's social and economic challenges, ensuring access to technologies and sustainability for the health system. The specific objectives were: i) to systematize studies that characterized translational research in medical devices; ii) map the challenges for the implementation of translational health research; iii) contribute to the design of institutional strategies; and iv) support the formulation of public policies. Methods: This study used the scoping review technique, according to PRISMA-ScR and the Joanna Briggs Institute guidelines. Concerning the extraction of relevant articles, the journals indexed in Bireme, Pubmed, Scopus, Web of Science, and Google Scholar were consulted for selecting relevant articles. The search was carried out on 11/28/2021, updated on 04/29/2022, and there were no restrictions as to the year of publication, language or type of analysis. Studies that did not answer the research question were excluded, as they dealt exclusively with the pharmaceutical segment, the translation of knowledge into clinical practice, or addressed the process of translational research applied to specific diseases or technologies. Results: Thirty-three articles were included indicating that the approach of translation of research is multidisciplinary and transdisciplinary and encompasses knowledge and aspects that go beyond basic and applied research and incorporates final steps concerning regulatory aspects, clinical research, market analysis, technology transfer, production and incorporation of technologies into the health system.